Pemberdayaan Kelompok Wanita Tani “Bukit Makmur” melalui Diversifikasi Produk Olahan Sayuran untuk Meningkatkan Ketahanan Ekonomi Keluarga di Kabupaten Majene - Nur Qamariah S; Andi Suryani Syamsuddin; Indayani B (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service program was carried out with the Women Farmers Group (KWT) Bukit Makmur in Pappota Village, Banggae Timur District, Majene Regency. The program was motivated by the limited knowledge, skills, facilities, and capital of the group in managing agricultural products, particularly vegetables. The method used was Participatory Action Research (PAR) through stages of socialization, training, mentoring, and participatory evaluation. The activities resulted in increased knowledge and skills of KWT members in vegetable processing, product diversification into value-added products such as spinach chips, vegetable nuggets, and instant seasoning, as well as the application of appropriate technologies such as a food dehydrator and vacuum sealer. In addition, the introduction of digital marketing strategies through social media and WhatsApp Business expanded the market reach of the products. This program has contributed to enhancing entrepreneurial motivation, household income, and family economic resilience. Therefore, this community service activity supports women’s empowerment, strengthens local food security, and contributes to the achievement of the Sustainable Development Goals (SDGs).